IMPLEMENTASI PENEMPATAN JABATAN PIMPINAN TINGGI PRATAMA (JPT) PEMERINTAH KABUPATEN JAYAPURA - Awig Pranowo; Apolo Safanpo (JURNAL KEBIJAKAN PUBLIK, 2021)
This study aims to find out the implementation of the primary high leadership position selection system (JPT) openly in jayapura district government and to parse the factors that hinder its implementation. The method in the study is a descriptive method with a qualitative approach. The data was collected with in-depth interviews with research informants. In addition, it is supported by field observations as well as through documenting. Informants are determined by purposive techniques. Data analysis includes reduction, presentation and drawing conclusions. The results of this study show that the implementation of JPT selection has not been in accordance with the objectives to be achieved. These factors are influenced by the lack of desire and motivation of the apparatus to participate in the selection. Another factor that causes the implementation does not go well is due to the low competitive spirit of the apparatus concerned accompanied by unpreparedness. While from asn from outside Jayapura district is due to the high cost of needs, inadequate aspects of facilities and infrastructure, as well as comfort factors in the current position. While other inhibitory factors indicate that communion to prospective selection participants has not been effective with a narrow scope.